Avaliação de Kerma na superfície de entrada da pele em pacientes pediátricos do Hospital de Clínicas de Curitiba - Porto, Lorena Elaine (2010)
In the present work absorbed doses by pediatric patients in chest radiographs were measured in 386 x-ray examinations in AP/PA and LAT projections. The patients were divided in age groups of 0-1 years, 1-5 years, 5-10 years and 10-15 years. The examinations were made at the pediatric room of Clinical Hospital of the Federal University of Paraná. Initially the entrance skin dose was measured with thermoluminescent dosimeters TLD-100 in 68 expositions, distributed in the age groups. The dose was also determined with the software dosimetric calculations that calculates the dose for each patient, from the X-ray equipment yield. The program uses the following data as input: patient mass, age, skin-focus, radiographic technique (kV, mAs), and the yield measurement made with an ionization chamber for calibration. The first evaluated data showed higher doses for the younger patients. A change in the radiographic technique of the examinations contributed to the reduction of the doses. The whole radiographic procedure was evaluated and, thus, showed that the radiographic technique had to be adjusted and the procedure as a whole had to be constantly optimized. Dates were measurement in 2007 again and after 2009. At a first moment the dose levels if had kept. In 2009 the values had come back to go up due to the increase of the load (mAs). The doses were then compared with the regulatory dose limits.